Promotion of digital reading: A case study among University office workers - Sánchez Sosa, Erika Rubi; Jarvio Fernández, Antonia Olivia; Ojeda Ramírez, Mario Miguel (IE Revista de Investigación Educativa de la REDIECH, 2021)
This work reports an intervention project to promote reading carried out with employees of the administrative areas of the Universidad Veracruzana (UV) in Mexico, some with a bachelor’s degree and others with a postgraduate degree. The intervention is framed in sociocultural theory and dialogism, under the action research methodology. Conceptual aspects of reading for pleasure, digital reading and the importance of their promotion are analyzed. Employees are familiar with information and communication technology (ICT) tools, therefore the proposal sought to take advantage and to expand these experiences. A blog was used to manage the readings, in addition to email and a social network to maintain close contact between the coordinator of the intervention project and the attendees. To reinforce dialogue and promote reading, 13 face-to-face sessions were held in the work areas. This made it possible to circumvent the limitation of the time available to the participants. The positive impact on the perception of digital reading for pleasure was verified from face-to-face and virtual dialogue. The group improved their cohesion and reading skills, beneficial aspects for the development of their activities and therefore for the institution where they work.